Characterization of the complete chloroplast genome and phylogenetic analysis of Pittosporum tobira (Pittosporaceae). Issue 2 (2nd April 2020) - Ling, Li-Zhen; Feng, Li-Ting; Luo, Yu-Lai; Zhang, Shu-Dong
Abstract: The first complete chloroplast (cp) genome sequences of Pittosporum tobira were reported in this study. The cp genome of P. tobira was 153, 754 bp long, which included a large single copy (LSC) region of 85, 010 bp and a small single copy (SSC) region of 18, 740 bp separated by two inverted repeat (IR) regions of 25, 002 bp. The cp genome of this species contained 113 unique genes, including 79 protein-coding genes, 30 transfer RNA genes and 4 ribosomal RNA genes. The overall GC content was 38.3%. Phylogenetic analysis of the complete cp genomes within the order Apiales suggested that P. tobira, the representative of Pittosporaceae, is sister to the families of Apiaceae and Araliaceae.